2015
DOI: 10.1042/bsr20140171
|View full text |Cite
|
Sign up to set email alerts
|

G-protein coupled receptor solubilization and purification for biophysical analysis and functional studies, in the total absence of detergent

Abstract: G-protein coupled receptors (GPCRs) constitute the largest class of membrane proteins and are a major drug target. A serious obstacle to studying GPCR structure/function characteristics is the requirement to extract the receptors from their native environment in the plasma membrane, coupled with the inherent instability of GPCRs in the detergents required for their solubilization. In the present study, we report the first solubilization and purification of a functional GPCR [human adenosine A2A receptor (A2AR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
177
0
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(193 citation statements)
references
References 42 publications
7
177
0
9
Order By: Relevance
“…Proteins within SMALPs have been shown to bind ligands comparably to those in the native membrane [44]. The use of SMALPs has facilitated improved thermostability and homogeneity of membrane proteins such as P-glycoprotein (P-gp) and the adenosine A2a receptor [39,42,44]. To date no crystal structure has been reported using SMALPs but both negative stain and cryo-EM low resolution structural maps have been determined [39,43].…”
Section: Smalpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins within SMALPs have been shown to bind ligands comparably to those in the native membrane [44]. The use of SMALPs has facilitated improved thermostability and homogeneity of membrane proteins such as P-glycoprotein (P-gp) and the adenosine A2a receptor [39,42,44]. To date no crystal structure has been reported using SMALPs but both negative stain and cryo-EM low resolution structural maps have been determined [39,43].…”
Section: Smalpsmentioning
confidence: 99%
“…During the formation of SMALPs from a biological membrane, membrane proteins can become trapped inside these discs (as shown in Figure 1D), solubilising them into small particles (much like nanodiscs when using membrane scaffolding proteins), but without the need for detergent at any stage. The proteins within a SMALP can be effectively purfied using affinity chromatography [39,[42][43][44]. The particles are stable once formed so there is no need to supplement buffers during purification as there is when using detergents; this is a major cost advantage.…”
Section: Smalpsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that this polymer is able to directly solubilize lipid membranes into nanodisk particles without the help of detergents. In this way, membrane proteins can be solubilized in their native lipid environment (4-7), which was found to help stabilize the protein (5,6,8). This has opened options to purify membrane proteins that are unstable in detergent micelles and to study native protein-lipid interactions by biochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…A further advantage of these so-called native nanodisks is that they are small, with sizes in the range of 10-25 nm (4)(5)(6)(9)(10)(11)(12)(13)(14)(15). This makes them suitable to be characterized by a variety of biophysical approaches including UV/Vis-and fluorescence spectroscopy (5,6,8), as well as light scattering techniques (6,14).…”
Section: Introductionmentioning
confidence: 99%